Remembering the Legacy of Judi Tuerck - Amy Morris; Cheryl Hermerath; Jelili Ojodu; Neil Buist (International Journal of Neonatal Screening, 2022)
Judith “Judi” Tuerck, RN, MS, one of the true pioneers in the development of newborn screening (NBS), passed away on Saturday, 18 June 2022 (Figure 1) [...]